Assinaturas isotópicas dos calcários fossilíferos da Formação Crato da Bacia Sedimentar do Araripe, Brasil: revisão, dados novos e implicações forenses - Sousa, Marcos Antônio Pimentel de (2024)
The Crato Formation is recognized as a Cretaceous lacustrine limestone rich in exceptionally well-preserved fossils (lagerstätte), containing several species of fossilized organisms, including vertebrates such as pterosaurs, dinosaurs, and anurans. Despite the Brazilian law prohibiting their commercialization since the 1940s, these fossils have been targeted by traffickers for decades. Accurate identification of fossil origin is crucial for the police investigations combating this trafficking that, in Brazil, is the responsibility of the Federal Police. This study aims to contribute to this effort by developing a practical, accurate, and minimally destructive method for identifying the origin of the large vertebrate fossils of the Crato Formation. The method relies on the analysis of stable carbon (ẟ13CV-PDB) and oxygen (ẟ18OV-PDB) isotopes in the host limestone. For that, the present study compiled data from both previously published research and new analyses, totalizing 239 samples. The analyses focused on progressively narrowing down the geographic and stratigraphic origin within the fossil-bearing layer. The Crato Formation is a formal, 70-meter-thick stratigraphic unit informally divided into six carbonate units (C1 to C6) from bottom to top. The lagerstätte is located in the uppermost unit (C6), which is about 10 meters thick. Within the C6 unit, large vertebrate fossils are assigned to a basal 2-meter level called the "sete cortes" layer. For comparison, the study also included isotopic data from lacustrine limestones of similar stratigraphic units from Brazil (Codó Formation) and the United States (Green River Formation), totalizing 26 samples. The results showed that the specific stratigraphic level within the Crato Formation containing the most valuable vertebrate fossils, the “sete cortes” layer, has statistically distinct and narrowly variable isotopic values. This distinctiveness is evident when compared to limestones from other basins and even from different sections within the same carbonate unit (C6). In this sense, the statistical patterns of ẟ18OV-PDB and ẟ13CV-PDB obtained for the "sete cortes" ethnostratum were, respectively: arithmetic averages of -5.9‰ and +0.9‰; standard deviations of 0.8 and 0.6; medians of -5.9‰ and +0.7‰; and interquartile ranges of 1.5 and 1.2. Hitherto, the presented method seems to have significant potential for both forensic investigations and tracing the specific stratigraphic origin of fossils eventually collected without proper documentation of their location.